2013
DOI: 10.2105/ajph.2012.301103
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Mortality Paradox: A Systematic Review and Meta-Analysis of the Longitudinal Literature

Abstract: To investigate the possibility of a Hispanic mortality advantage, we conducted a systematic review and meta-analysis of the published longitudinal literature reporting Hispanic individuals' mortality from any cause compared with any other race/ethnicity. We searched MEDLINE, PubMed, EMBASE, HealthSTAR, and PsycINFO for published literature from January 1990 to July 2010. Across 58 studies (4 615 747 participants), Hispanic populations had a 17.5% lower risk of mortality compared with other racial groups (odds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
263
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(283 citation statements)
references
References 77 publications
16
263
2
2
Order By: Relevance
“…Finally, an example in the domain of physical health is the putative ''Hispanic paradox'' in the United States: Hispanics have a lower risk of mortality than non-Hispanic Whites and Blacks, despite relatively lower socioeconomic status (Ruiz et al 2013).…”
mentioning
confidence: 99%
“…Finally, an example in the domain of physical health is the putative ''Hispanic paradox'' in the United States: Hispanics have a lower risk of mortality than non-Hispanic Whites and Blacks, despite relatively lower socioeconomic status (Ruiz et al 2013).…”
mentioning
confidence: 99%
“…One line of results emphasizes their positive health and the protective features of ethnicity and culture as evidenced by the Hispanic and Mexican immigrant health paradox. This refers to the counterintuitive finding that despite high risks associated with poverty, discrimination and poor healthcare access, Hispanic immigrants have far better health and mental health indicators than nonHispanic Whites (Ruiz, Steffen & Smith, 2013). For example, data from 6 776 individuals in the National Comorbidity Survey Replication and the National Latino and Asian American Study found that Mexican immigrants had lower rates of depression anxiety, and substance use disorders than the general population (Alegria et al, 2008).…”
Section: Mental Health Among Mexican Immigrantsmentioning
confidence: 99%
“…Given that Mexican immigrants can spend an extended period of years without their mental health being adversely affected, it is important to examine the sources of the initial resilience of immigrants and to identify factors that may prevent the erosion of their health (Breslau et al, 2006;Franzini, Ribble & Keddie, 2001;Morales, Lara, Kington, Valdez & Escarce, 2002;Ruiz et al, 2013). Determining the sources of their resilience calls for the consideration of alternative perspectives that can offer additional information for a broader comprehension of the health of this group.…”
Section: Mental Health Among Mexican Immigrantsmentioning
confidence: 99%
“…[19][20][21] This epidemiological contradiction, known as the Latino Paradox, explains the notion that Latinos have lower mortality rates than Whites, 22 albeit while experiencing greater barriers to health care and higher rates of chronic conditions like diabetes. 14,15,23 To this end, some studies introduce various control variables to isolate the effects of Latino status, 20,24,25 and find that the apparent mortality advantage suggested by the Latino Paradox does not exist for conditions like diabetes. 26 Diabetes is the fifth leading cause of death among Latinos and is 66%…”
Section: Introductionmentioning
confidence: 99%